(untitled) (Web of Teachers: Inderscience Research, 2025)
The article highlights the methodology of organizing and conducting pedagogical experimental studies. It explains the stages of forming experimental and control groups, developing methodological materials, organizing experimental activities, selecting diagnostic tools, and analyzing results on a scientific basis.